THE URGENCY OF ATTACHING FINGERPRINTS TO THE DEED MINUTES IN RELATION TO THE AMENDMENT OF THE NOTARY OFFICE LAW - Desak Nyoman Citra Mas Saraswati; Pande Yogantara S. (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
The main objective of this research is to determine and analyze the legal certainty of fingerprint attachment in the Notarial Deed Minute and the related urgency and implications in the event of a dispute in the minute without fingerprint attachment related to the UUJN-P. The method used in this research is a normative juridical method with a focus on legislative approach and conceptual approach, using a technique of analyzing legal materials through description, systematic, interpretation, and argumentation. The results of this research indicate that changes in the regulation regarding the obligation to attach fingerprints in the UUJN-P need to be supplemented with implementing regulations in order to create legal certainty and minimize multiple interpretations in its application procedure. The attachment of fingerprints in the minute does not affect the authenticity of the deed, as the authenticity of a deed is determined by the fulfillment of Article 1320 of the Civil Code, Article 1868 of the Civil Code, and Articles 38-53 of the UUJN-P. In terms of proof, both the minute with fingerprint attachment and the minute without fingerprint attachment have the same evidentiary strength, as they are still considered authentic deeds. The attachment of fingerprints in the minute can serve as evidence in court proceedings to support the cautious principle of notaries in case of signature forgery.